Potential Development of Trans Central Java Bus Rapid Transit (BRT) Corridor 1 Towards Sustainable Mobility - Suwarno Suwarno; Muhamad Iqbal Sarifudin; Titus Hari Setiawan; Juanita Juanita (Automotive Experiences, 2023)
The Bus Rapid Transit (BRT) in the Banyumas area, Central Java, aims to provide inter-regional connectivity in Purwokerto City and Purbalingga Regency. This is one of the six BRT corridors in Central Java launched in 2018. Therefore, this study aims to examine the development of BRT corridors based on transit-integrated land use along the corridor, after five years of operation. The primary survey was conducted on land use along the corridor at a radius of 200 m and 400 m from the BRT bus stop, which was analyzed using a qualitative descriptive method. As a result, BRT Corridor 1 in Central Java can be identified for bus-based transit development. First, BRT services have connected high to very high populations. Second, BRT shelters have good access to shopping centers, culinary centers, and artificial tourism within a 200 m and 400 m radius. Third, BRT shelters are also connected to other modes of public transportation. However, the results of our study found that the BRT shelters had not been connected to pedestrian facilities. Based on these three criteria, BRT Corridor 1 in Central Java is feasible to be developed as a sustainable public transport service. However, further studies are needed to link BRT shelters with pedestrian facilities, in order to create clean and sustainable mobility.